2018
DOI: 10.3389/fnsyn.2018.00012
|View full text |Cite
|
Sign up to set email alerts
|

A Focus on Reward Prediction and the Lateral Habenula: Functional Alterations and the Behavioral Outcomes Induced by Drugs of Abuse

Abstract: The lateral habenula (LHb) regulates reward learning and controls the updating of reward-related information. Drugs of abuse have the capacity to hijack the cellular and neurocircuit mechanisms mediating reward learning, forming non-adaptable, compulsive behaviors geared toward obtaining illicit substances. Here, we discuss current findings demonstrating how drugs of abuse alter intrinsic and synaptic LHb neuronal function. Additionally, we discuss evidence for how drug-induced LHb alterations may affect the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 82 publications
2
22
0
Order By: Relevance
“…We previously showed that acute nicotine induces an increase of the LHb neuronal activity in vivo [42] that might be related to its noxious/aversive effect [29,47] and reduced rewarding effect by inhibiting VTA dopaminergic neurons via the rostromedial tegmental neurons [48]. Here we found that 5-HT 2A Rs are overexpressed in the LHb after exposure to acute nicotine and TCB-2 administration induces mainly inhibitory effects on LHb neurons of acute-treated animals.…”
Section: Discussionmentioning
confidence: 50%
“…We previously showed that acute nicotine induces an increase of the LHb neuronal activity in vivo [42] that might be related to its noxious/aversive effect [29,47] and reduced rewarding effect by inhibiting VTA dopaminergic neurons via the rostromedial tegmental neurons [48]. Here we found that 5-HT 2A Rs are overexpressed in the LHb after exposure to acute nicotine and TCB-2 administration induces mainly inhibitory effects on LHb neurons of acute-treated animals.…”
Section: Discussionmentioning
confidence: 50%
“…Genes harboring genetic loci that were associated with major depressive disorder in the largest genetic study to date were not enriched in the medial or lateral habenula ( Wray et al, 2018 ). This enrichment for depressive symptoms and the central role of the habenula in the hedonic neurocircuit motivated an analysis of genes that were differentially expressed in a study of well-being ( Graziane et al, 2018 ). Genes that were up-regulated in the blood of people with low levels of hedonic well-being were enriched in both divisions of the adult habenula (33 genes, p < 0.0005, AUROC > 0.67, specificity rank < 7, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, following repeated exposure to morphine, there are increases in norepinephrine-induced modulation of the extended amygdala (Aston-Jones et al, 1999 ; Delfs et al, 2000 ; Smith and Aston-Jones, 2008 ), activation of the amygdalar corticotrophin-releasing factor (CRF) system (Heinrichs et al, 1995 ; Maj et al, 2003 ), norepinephrine release in the extended amygdala (Fuentealba et al, 2000 ; Aston-Jones and Harris, 2004 ), and decreases in dopamine transmission (Diana et al, 1995 ). Also, following repeated exposure to cocaine, the lateral habenula, a brain region whose increased activity is correlated with aversive states (Graziane et al, 2018 ), has increased activation 15 min after repeated cocaine administration (Jhou et al, 2013 ), with evidence suggesting that this increase in cocaine-induced lateral habenula activation lasts until abstinence day 2 in rodents with a history of cocaine self-administration (Neumann et al, 2014 ). Additionally, lateral habenula neuronal firing is increased in vivo during ethanol-induced conditioned taste aversion (Tandon et al, 2017 ).…”
Section: Neurobiology Of Drug-induced Cpp: Focus On Opioid Cppmentioning
confidence: 99%